Effect of Conservative Interventions for Musculoskeletal Disorders in Preprofessional and Professional Dancers: A Systematic Review - Justine Benoit-Piau; Christophe Benoit-Piau; Nathaly Gaudreault; Mélanie Morin (International Journal of Sports Physical Therapy)
# Background